A multi-scale diffusional-mechanically coupled model for super-elastic NiTi shape memory alloy wires in hydrogen-rich environment. (June 2023) - Yu, Chao; Jiang, Han M; Song, Di; Zhu, Yilin; Kang, Guozheng
Highlights: A multi-scale diffusional-mechanically coupled constitutive model is constructed for NiTi SMA wires in H-rich environment. In the grain scale, a crystal plasticity-based constitutive model is established within the framework of irreversible thermodynamics. In the polycrystalline aggregate scale, a diffusional-mechanically coupled self-consistent homogenization method is developed to measure the interaction among the grains. An assumption of uniform stress field in the macroscopic scale is adopted to achieve the scale transition from the polycrystalline aggregate to the whole wire. Super-elastic deformation of NiTi SMA wires after H charging can be well described. Abstract: The functional devices made by NiTi shape memory alloys (SMAs) are often serviced in hydrogen (H)-rich environment. Recently experimental results showed that the martensite transformation (MT) of NiTi SMA changed strongly after charging H, which originates from the H diffusion in the material and an additional transformation resistance caused by the absorbed H atoms. In this work, a multi-scale diffusional-mechanically coupled constitutive model is constructed to describe the super-elastic deformation of NiTi SMA wires in H-rich environment. In the grain scale, a crystal plasticity-based constitutive model is developed within the framework of irreversible thermodynamics. Four deformation mechanisms, i.e., elasticity, MT, transformation-induced plasticity (TRIP) and H expansion are taken into account. Since the H atoms can be trapped by the lattice defects, the total H concentration is further decomposed into two parts, i.e., the lattice hydrogen concentration and the trapped one. The generalized thermodynamic forces of MT and TRIP are derived from the Gibbs free energy and Clausius-Duhem inequality. The evolution of H concentration field is derived by combining the chemical potential, diffusion balance equation and the Fick's law. In the polycrystalline aggregate scale, in order to measure the interaction among the grains and obtain the overall response of the polycrystalline aggregate, a diffusional-mechanically coupled self-consistent homogenization method is developed. Meanwhile, the finite volume method is employed to calculate the H concentration in each grain. An assumption of uniform stress field in the macroscopic scale is adopted to achieve the scale transition from the polycrystalline aggregate to the whole wire. To validate the prediction capability of the proposed model, the predictions are compared with the experiments. Moreover, the influences of loading rate on the deformation of the wires in the process of in-situ charging H are predicted and discussed.